2021
DOI: 10.26434/chemrxiv.13124993
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Imputation of Missing Gas Permeability Data for Polymer Membranes using Machine Learning

Abstract: <p><a>Polymer-based membranes can be used for energy efficient gas separations. Successful exploitation of new materials requires accurate knowledge of the transport properties of all gases of interest. An open source database of such data is of significant benefit to the research community. The Membrane Society of Australasia (https://membrane-australasia.org/) hosts a database for experimentally measured and reported polymer gas permeabilities. However, the database is incomplete, limiting its po… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 39 publications
0
9
0
Order By: Relevance
“…N.b. recommendation systems have been built for use in the chemical sciences to impute missing gas permeabilities in polymers [71], antiviral activities of molecules [72], and stabilities of inorganic materials [73,74].…”
Section: Review Of Previous Workmentioning
confidence: 99%
See 1 more Smart Citation
“…N.b. recommendation systems have been built for use in the chemical sciences to impute missing gas permeabilities in polymers [71], antiviral activities of molecules [72], and stabilities of inorganic materials [73,74].…”
Section: Review Of Previous Workmentioning
confidence: 99%
“…Loosely related, meta-learning has been used to predict an adsorption property of materials at different conditions by learning an intermediate representation of the material based only on available adsorption data. 78 N.b., recommendation systems have been built for use in chemical sciences to impute missing gas permeabilities in polymers, 79 antiviral activities of molecules, 80 and stabilities of inorganic materials. 81,82…”
Section: Introductionmentioning
confidence: 99%
“…The calculated molecular features are then used as inputs for multitask ML models and trained to learn gas permeabilities ( 56 , if at least one gas permeability is available. We use their source code to impute missing gas permeabilities to augment our dataset.…”
Section: Training and Interpretation Of Supervised ML Modelsmentioning
confidence: 99%
“…We utilize two representations for the polymer repeating unit, namely chemical descriptors as generated by RDKit 54 (listed in Table S1 of Supporting Information) and the Morgan fingerprint with frequency (MFF) 55 . We impute missing permeabilities using multivariable imputation by chained equations (MICE) 56 , and we then train multitask supervised ML models to establish synthesis-property relations for these polymer membranes. While various supervised ML models have been used in polymer informatics, including recurrent neural networks, support vector machines, gaussian processes, and others, we choose to focus our study to random forest (RF) regression and deep neural networks (DNN), which have demonstrated outstanding performance in our recent benchmark study 44 .…”
Section: Introductionmentioning
confidence: 99%
“…Our work is not the first machine-learned recommendation system for use in the chemical sciences. Yuana et al [74] imputed missing gas permeability in polymers. Sosnia et al [75] developed a recommendation system for antiviral drugs by learning a low rank model of a compound-virus activity matrix.…”
Section: Placing Our Work In Contextmentioning
confidence: 99%